2019
DOI: 10.1002/srin.201800523
|View full text |Cite
|
Sign up to set email alerts
|

On the Optimization of Microstructure and Mechanical Properties of CrWMn Tool Steel by Deep Cryogenic Treatment

Abstract: The authors explore here the influence of cryogenic treatment on the microstructure and mechanical properties of CrWMn tool steel. Compared to the normal quenching and tempering process, the tensile strength, toughness, and hardness is enhanced after quenching‐cryogenic‐tempering treatment. The result is attributed to the high number density of precipitated ultra‐fine small granular carbide (SGC), the transformation of retained austenite, and the refinement of the martensite. Two types of retained austenite (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Deep cryogenic treatment (DCT) is a sub-zero treatment where materials are exposed to temperatures below −125 • C with liquid nitrogen being the preferred cooling media [1]. Deep cryogenic treatment on martensitic steels is commercially carried out to improve wear resistance [2][3][4][5][6][7], and it has also been reported to affect other material properties such as hardness [8][9][10][11][12][13][14][15][16][17][18][19][20] and tensile strength [21][22][23]. There are some proposed mechanisms for these improvements in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Deep cryogenic treatment (DCT) is a sub-zero treatment where materials are exposed to temperatures below −125 • C with liquid nitrogen being the preferred cooling media [1]. Deep cryogenic treatment on martensitic steels is commercially carried out to improve wear resistance [2][3][4][5][6][7], and it has also been reported to affect other material properties such as hardness [8][9][10][11][12][13][14][15][16][17][18][19][20] and tensile strength [21][22][23]. There are some proposed mechanisms for these improvements in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The transformation of retained austenite (RA) to martensite is one of the primary objectives of DCT, and it is one of the predominating proposed mechanisms for improvement in wear resistance, as the martensitic phase is much harder than the parent austenite phase [2,4,19]. This transformation has regularly been quantified and verified via X-ray diffraction (XRD) [3,4,19,22,[24][25][26][27][28][29][30]. However, it has also been observed that alloys that are already fully martensitic can exhibit markedly improved wear resistance after DCT, even though there is no change to the martensite volume fraction [31]; this is commonly referred to as the conditioning of the martensite [32].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is one of the theoretically explained mechanisms for wear resistance increasing because the martensitic phase has much higher hardness than the initial austenite phase [31]. Typically, this phase transformation has been investigated and quantified via the X-ray diffraction (XRD) method [32][33][34][35]. The authors of this work used such a method, along with an ultrasonic method and electron microscopy with a microanalyzer, to observe the transformations of RA.…”
Section: Introductionmentioning
confidence: 99%